(untitled) (Research, Society and Development, 2021)
Introduction: Socioeconomic and racial differentials and access to prevention, diagnosis and early treatment measures have increased mortality from prostate cancer. Objective: Describe mortality from prostate cancer in the State of Maranhão, according to socioeconomic and demographic variables. Methods: Descriptive study with 4,238 deaths from prostate cancer, CID 10-C61, which occurred from 2000 to 2017 among men ≥40 years old. The absolute and relative frequencies were estimated. Age curves of proportional mortality by color/race and age, and box-plot for the age of death by color/race were drawn up. Results: Prostate cancer accounted for 20.0% of deaths from cancer. Predominates among browns,> 80 years old, with low education, with death at home and in the region outside the capital São Luís. There was a worse mortality structure for browns and blacks in all years, with a median age of death lower than in whites. Conclusions: There was a profile of individual and contextual characteristics associated with deaths, indicating the need for actions broader prevention, diagnosis and treatment of this cancer.